Magyarország asszimilációs politikája a kultúra és az oktatás területén a Horthy-korszakban - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The issue of developing the institutional system of public education significantly determined the area of Hungarian cultural policy in the period following the First World War. As a result of the territorial losses, the reorganisation of the public education system became necessary from an administrative position. Kunó Klebelsberg’s institutional development certainly has to be appreciated but it must be added that establishing cultural supremacy as a cultural policy goal is more debatable, since it proclaimed the superiority of the Hungarian nation over both the surrounding peoples and the minorities living in the country, towards whom the assimilation policy could be manifested. During Bálint Hóman’s ministership, the emphasis was placed even more strongly on national education, which brought to the fore the need for state supervision. The supervision of the teachers was performed by school district directors, who played an important role in the centralisation of education and also the implementation of the “Jewish Laws” regarding schools. According to the practice in Baranya County, it can be concluded that the educational authorities of Baranya tried to act fairly in the given circumstances, and sometimes they were satisfied with less evidence of the teacher’s origin. This procedure applies to the authorities of Baranya County, especially the in the field of education among them, since the research of local practice focused on this area based on archival documents. The Hungarian-German cultural convention of 1936 provided a framework for the expansion of cultural policy. Hungarian authors such as Hóman, Paikert and Willer published their thoughts in German on the relationship between the two countries, on common roots, on forms of cultural cooperation and on the issues of national education and minority and assimilation policy. Hungarian writers also emphasized the importance and benefits of the bond with Germany. As the writings on cultural policy and their publication in German showed, the assimilation policy was also manifested towards the nationalities that remained in the country after Trianon. Practical examples illustrate the central education policy through the work of Ferenc Balázs, rapporteur of minority education, who served directly under the administration of the Ministry of Religion and Education between 1938 and 1944. Due to the situation of the schools he reviewed, the local development of nationalities’ education and the difficulties of implementation, especially with regard to the so-called unified education system and then the full native language education, can be more comprehensively understood.